Digitization in Production: A Timely Opportunity - Adusumalli, Harshini Priya (Engineering International, 2016)
Using modern digital technology, the production team aspires to innovate and enhance existing procedures. However, the majority of the time, information about these new technology exists outside of a company's walls. The idea of absorptive capacity, as well as literature on open innovation, are used by the authors to investigate the function of external search in the digitalization of the manufacturing industry. Companies in the manufacturing industry who want to digitize their processes can profit from inbound open process innovation, but the effectiveness of this approach differs depending on which cluster of digital technologies is being used. In general, the findings imply that enterprises should focus on developing strong links with a small number of external knowledge partners rather than maintaining superficial relationships with a large number. An investigation of the relationship between enterprises' external search and their use of digital technology is presented in this paper, which contributes to the expanding body of literature on the digitalization of manufacturing. It contributes to the literature on open process innovation by providing early empirical insights.
Keywords: Digitization; Innovation; Process Innovation; Industry Revolution